2019
DOI: 10.32598/jccnc.5.4.93.12
|View full text |Cite
|
Sign up to set email alerts
|

uberty Health Education and Female Students’ Self-efficacy

Abstract: Background: Adolescence is an essential period in every human’s life. The lack of knowledge on puberty issues may adversely impact an adolescent’s future mental health and self-efficacy. The present study aimed to determine the effect of puberty health education on the general self-efficacy of female students. Methods: This was a quasi-experimental study with a pre-test; post-test and a control group design. This study was conducted on 100 female students of public schools with the onset of menstruation in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…After educational interventions, most students can comply with health tips during puberty such as proper nutrition during menstruation, importance of daily exercise, hygiene of the genital area, sufficient sleep and rest, bathing, purity after defecation, hygiene during menstruation, treatment of menstrual pain, and premenstrual syndrome. The findings were consistent with previous studies [ 18 , 29 ]. Although in the control group, the difference in scores for constructs of perceived severity, benefits, barriers, and self-efficacy before and after the intervention was statistically significant, this difference was small.…”
Section: Discussionsupporting
confidence: 94%
“…After educational interventions, most students can comply with health tips during puberty such as proper nutrition during menstruation, importance of daily exercise, hygiene of the genital area, sufficient sleep and rest, bathing, purity after defecation, hygiene during menstruation, treatment of menstrual pain, and premenstrual syndrome. The findings were consistent with previous studies [ 18 , 29 ]. Although in the control group, the difference in scores for constructs of perceived severity, benefits, barriers, and self-efficacy before and after the intervention was statistically significant, this difference was small.…”
Section: Discussionsupporting
confidence: 94%
“…In the mentioned study, it was suggested that by providing education to students, it can improve their self-efficacy by providing learners with education. [ 41 ] Our study is consistent with the desired studies.…”
Section: Discussionsupporting
confidence: 92%
“…This result indicates the significance of self-efficacy in the success of health behaviors. [ 41 ] According to the current study findings, there was a considerable difference in the self-efficacy scores between the intervention and control groups immediately after and 1 month after the intervention. Self-efficacy significantly increased in the test group after providing the study intervention.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, only 48.3% of them had access to this information [9]. In many societies, young people have limited access to the right information because their parents either lack the requisite knowledge and skills to teach them or parents are either busy or feel embarrassed to discuss reproductive health with their children [10]. Similarly, Pillitteri suggests that young people rarely talk to health personnel about sensitive issues because they often receive their information from peers and friends [11].…”
Section: Introductionmentioning
confidence: 99%